The Optimum Portfolio of Sharia Stocks in Indonesia - Waluyo, Dwi Eko; Astuti, Sih Darmi; Goh, Gerald Guan Gan (IKONOMIKA, 2023)
This research investigates whether optimizing stock portfolios aligns with prudence in Sharia-compliant stock investment. It compares the portfolio optimization analysis between Sharia-compliant securities and the Jakarta Islamic Index. Each group is structured with its optimal portfolio composition to achieve the highest expected return for various possible risks. Two efficient frontiers are derived from both optimal portfolios. A slight intersection is found in the efficient frontier between these two portfolio groups, justifying that taking high risks in one group results in a low-risk choice in the other portfolio group. The Sharia-compliant investment is realized by choosing an optimal portfolio with low risk while still tolerating investment selections with higher risk, as long as they are aligned with Islamic principles. The findings of this optimal portfolio offer practical guidance for investment decisions and significantly contribute to advancing the field of Islamic finance and investment practices.